PTU-070 Selecting the most Cost-Effective Model of Care for Delivering Biological Agents as Maintenance Therapy in Patients with Crohn'S Disease. (4th June 2013) - Lougher, E; Allison, M C; Hodson, K; Pugh, M
Abstract : Introduction: The introduction of anti-TNF alpha monoclonal antibodies in 1999 has revolutionised the management of inflammatory bowel disease (IBD). A significant increase in gross spend on biological agents in the management of Crohn's disease has occurred since the implementation of NICE guidance in 2002. The unplanned nature of the service expansion and evolution has led to a wide variation in service delivery. Within the Aneurin Bevan Local Health Board (ABHB) the approximate doubling in the gastroenterology spend on biologics (between 2010 and 2011) prompted a review of current services and an investigation of other potential models of care for delivering the service. Methods: A service evaluation for both adalimumab and infliximab (IFX) including: an assessment of the current services from a patient's perspective (study 1), identifying and exploring models of care for delivering the service (study 2) and evaluating the costs associated with each model of care (study 3) was undertaken. Study 1 comprised face-to-face semi-structured, tape recorded patient-interviews, which were transcribed verbatim and then thematically analysed. Study 2 utilised a number of methods to identify key-informants at various secondary care sites to participate in telephone semi-structured interviews, models identified were compared and contrasted. Study 3 identified and compared the costs of current models within ABHB with viable models identified in study 2. Results: The results revealed overall satisfaction with the IBD services within ABHB and with the service provided by Healthcare at Home Ltd. Patients were complementary of the IBD team and the telephone help line. Nonetheless areas for improvement with regards to the infusion facilities were identified by the IFX group. Study 3 identified four models of care: IFX prepared in pharmacy, IFX prepared by a specialist nurse, IFX at home and adalimumab at home. For standard dosing (79kg patient-average IFX patient weight at ABHB) annual costs were £12, 237, £12, 314, £10, 254 and £9, 156 respectively, inclusive of pharmacy production time, nursing time and active drug and exclusive of hospital facilities. Vial sharing would reduce the cost of models one and two, however would require complex re-organisation to facilitate "pairing" patients. Study 3 identified adalimumab via Healthcare at Home as being the most cost-effective model. Conclusion: Where clinically appropriate adalimumab via Healthcare at Home Ltd is recommended for this group of patients within ABHB, with IFX via a home care company as second line. Work should be done to improve the current infusion facilities. Future work should include reviewing the potential of setting up a biologics unit shared between specialities. Disclosure of Interest: None Declared